Human shields, missiles, negative homesteading and libertarianism - Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
When a bad guy throws one innocent person against another, or uses one as a body shield so as to facilitate murdering the other, or is in the process of bashing in the heads of two such people, what are the rights and responsibilities of each of these latter two victimized parties vis a vis each other? The concept of negative homesteading is introduced in an attempt to shed light on these legal puzzles.
Keywords: libertarianizm; samoobrona; negatywne środowisko